The relationship of some non-intellective factors to academic achievement of the students of the Samar National School enrolled for the schoolyear 1977-1978 - Advincula, Elenita Liad (1978)
This study determined the extent of the relationship between study habits and attitudes and some personality factors with academic achievement and to establish a personality profile of the third year and fourth year students of the Samar National High School enrolled for the school year 1977-1978. The subjects were 300 students enrolled at the said school. The Brown-Holtzman Survey of Study Habits and Attitudes (SSHA),the High School Personality Questionnaire (HSPQ), and the Money Problem Checklist (MPCL) were used to gather data. It was concluded that study habits and attitudes are definitely correlated with academic achievement and of the personality factors, but only the following were found to be significantly correlated: conformity, leadership, and family relationship. Mood, emotional stability and sociability are not related to academic achievement. Students should be motivated to develop good study habits and attitudes, particularly those in the lower years.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Samar National School -- Students; Academic achievement